Optimal Design of Gorlov Turbine Using Computational Fluid Dynamics and Taguchi Method - Medyawanti Pane; Riswanton Saragih (Universitas Sultan Ageng Tirtayasa, 2024)
Wind energy for electricity generation presents a promising alternative to fossil fuels, driving the development of renewable energy technologies. Computational Fluid Dynamics (CFD) stands out as a powerful tool in this domain. This study focuses on optimizing the design of Gorlov turbines through a combination of CFD simulations and the Taguchi method. The research identifies four key factors influencing turbine performance: twist angle, chord length, number of blades, and aspect ratio. These factors are systematically varied using an orthogonal array, resulting in nine distinct blade configurations. Subsequently, simulations are conducted using ANSYS Fluent software under transient conditions at a wind speed of 5 m/s. Simulation results reveal that the maximum angular velocity achieved is 29.8187 deg/s, accompanied by a torque of 0.426 Nm, leading to a calculated maximum power output of 12.73 Watts. Furthermore, Taguchi analysis and ANOVA are employed to assess the significance of each factor. The analysis highlights the aspect ratio as the most influential factor, accounting for 99.7% of the observed variation. This study underscores the potential of CFD and the Taguchi method in optimizing wind turbine design for enhanced performance. The findings emphasize the critical role of the aspect ratio in determining turbine efficiency, paving the way for more efficient renewable energy generation.